SharePoint 2013 site owner - Jesperson, Ryan, Dr.; Safari eBooks ([Place of publication not identified] : CompuWorks, 2016)
"This course is designed to teach students an overview of SharePoint Site Owner roles and responsibilities. Students will learn to add and configure sites, create and configure libraries and lists, create and customize columns, and manage content types. Students will also learn to manage permissions and permission levels, create and modify site pages and work with navigation and regional settings."--Resource description page.
Title from resource description page (Safari, viewed September 8, 2016).
Presenter, Ryan Jesperson.
Keywords: Microsoft SharePoint (Electronic resource); Intranets (Computer networks); Web servers; Electronic books